Trajetórias de estudantes universitários (as) indígenas - Castorino, Adriano Batista (2014)
This thesis is the result of a job that was made in the Universidade Federal do Tocantins, with the quota program for indigenous students. The outline that guides this work is designed to broaden the research I did on this same topic for my dissertation, made in April 2011. Therefore, in August 2011 beginning the doctoral program in which I developed the following text. For this, I decided to broaden the scope of analysis and I dedicated myself to find mechanisms that would allow me to meet other indigenous education projects. After then, I went to the Faculdade Indígena Intercultural da Universidade do Estado de Mato Grosso. In addition, the proposed project a trip to Mexico to meet some projects intercultural universities in that country. I also looked for mechanisms that would allow me to go to Mexico. There met the Universidade Intercultural do Chiapas. My initial goal in developing this work is to meet the trajectory, or the life trajectories of indigenous students entering the university. So do not put the focus in the discussion of models of education offered. Before I make a tour of the very idea of the university in the western world. I opt for this method to elucidate that independent of the university or higher education model, there are elements that do not change, as the predominance of meritocracy and closed curricula. From this premise, turn me on experiences with indigenous students with whom I noticed as there is a discontinuity in their ways of seeing the world from the moment they enter the university. The impact of vocational training, the idea of profession somehow alters the relationship with the culture and way of life of the village. In UFT, I travel with some students to their villages and realize the amount of nostalgia that has the home and their relatives. In Unemat could live with students who stay longer than 30 days outside their villages. It is notoriously difficult to remain in the classroom after days away from home. In Unich realized how this is a recurring fact of the absence of family and relatives, even if there is a university almost exclusively indigenous